Effect of weed management and seed rate on crop growth under direct dry seeded rice systems in Bangladesh - Ahmed, Sharif; Salim, Muhammad; Chauhan, Bhagirath S. (Public Library of Science, 2014)
Weeds are a major constraint to the success of dry-seeded rice (DSR). The main means of managing these in a DSR system is through chemical weed control using herbicides. However, the use of herbicides alone may not be sustainable in the long term. Approaches that aim for high crop competitiveness therefore need to be exploited. One such approach is the use of high rice seeding rates. Experiments were conducted in the aman (wet) seasons of 2012 and 2013 in Bangladesh to evaluate the effect of weed infestation level (partially-weedy and weed-free) and rice seeding rate (20, 40, 60, 80, and 100 kg ha−1) on weed and crop growth in DSR. Under weed-free conditions, higher crop yields (5.1 and 5.2 t ha−1 in the 2012 and 2013 seasons, respectively) were obtained at the seeding rate of 40 kg ha−1 and thereafter, yield decreased slightly beyond 40 kg seed ha−1. Under partially-weedy conditions, yield increased by 30 to 33% (2.0–2.2 and 2.9–3.2 t ha−1 in the 2012 and 2013 seasons, respectively) with increase in seeding rate from 20 to 100 kg ha−1. In the partially-weedy plots, weed biomass decreased by 41–60% and 54–56% at 35 days after sowing and at crop anthesis, respectively, when seeding rate increased from 20 to 100 kg ha−1. Results from our study suggest that increasing seeding rates in DSR can suppress weed growth and reduce grain yield losses from weed competition.